Diseño de un plan de negocios para la exportación de uchuva liofilizada hacia Ámsterdam-Holanda (2020)
This document presents the design of a business plan for the export of lyophilized Goldenberry to Amsterdam - Holland. In this case, it continues to demonstrate the financial viability of the country, giving a starting point with a description of the conditions of the merchandise with respect to exotic and processed fruits in Colombia. Then, the technical-economic parameters were established, that is, everything that involves the description of the product until the export logistics, which allowed characterizing the project and knowing the amount of investment necessary for the export. Finally, if you created a project after 5 years of operation and if you determined the economic viability of the business plan, by means of reliable indicators such as the net present value, the internal pocket of return and finally the recovery time of the investment.